INTERNATIONAL STANDARDS AS CORPORATE GOVERNANCE MECHANISMS AND CREDIBILITY GAP IN JORDAN FINANCIAL MANAGERS' POINT OF VIEW. Issue 1 (2016) - Srouji, Anan Fathi; Halim, Mohd Suberi Ab; Lubis, Zulkarnain; Hamdallah, Madher Ebrahim
No abstract available